Have policy process scholars embraced causal mechanisms? A review of five popular frameworks. (April 2021) - van der Heijden, Jeroen; Kuhlmann, Johanna; Lindquist, Evert; Wellstead, Adam
Over 30 years, several key frameworks and theories of the policy process have emerged which have guided a burgeoning empirical literature. A more recent development has been a growing interest in the application of a 'causal mechanism' perspective to policy studies. This article reviews selected theories of the policy process (Multiple Streams Approach, Advocacy Coalition Framework, Punctuated Equilibrium Theory, Narrative Framework Theory, and Institutional Analysis and Development Framework) and reports on an exploratory meta-analysis and synthesis to gauge the take-up of causal-mechanistic approaches. The findings suggest that there has been limited application of causal mechanisms and calls for more theoretical and empirical work on that aspect. Given the overlapping frameworks exploring different aspects of the policy process, further research informed by causal-mechanism approaches points to a new generation of inquiry across these and other policy process theoretical frameworks.